2017
DOI: 10.1523/jneurosci.1031-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Plasticity in Accessory Olfactory Bulb Interneurons following Male–Male Social Interaction

Abstract: Chemosensory information processing in the mouse accessory olfactory system guides the expression of social behavior. After salient chemosensory encounters, the accessory olfactory bulb (AOB) experiences changes in the balance of excitation and inhibition at reciprocal synapses between mitral cells (MCs) and local interneurons. The mechanisms underlying these changes remain controversial. Moreover, it remains unclear whether MC-interneuron plasticity is unique to specific behaviors, such as mating, or whether … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 75 publications
3
48
0
Order By: Relevance
“…Future studies of AOB interneurons in vitro or in vivo including these simple intrinsic "fingerprinting" protocols will be able to compare the physiological profiles observed in each cell to those observed in this study. This approach supports the identification of novel physiological types or specific changes to established functionally-defined types that may occur in response to chemosensory experience (Cansler et al, 2017) and/or neuromodulation (Smith et al, 2009;Smith and Araneda, 2010;Leszkowicz et al, 2012). Taken as a whole, these results provide a major improvement in the available physiological data for AOB interneurons, and improve the foundation for studies of AOB circuit function.…”
Section: Implications Of Current Work For Models Of Aob Circuit Functionsupporting
confidence: 60%
See 3 more Smart Citations
“…Future studies of AOB interneurons in vitro or in vivo including these simple intrinsic "fingerprinting" protocols will be able to compare the physiological profiles observed in each cell to those observed in this study. This approach supports the identification of novel physiological types or specific changes to established functionally-defined types that may occur in response to chemosensory experience (Cansler et al, 2017) and/or neuromodulation (Smith et al, 2009;Smith and Araneda, 2010;Leszkowicz et al, 2012). Taken as a whole, these results provide a major improvement in the available physiological data for AOB interneurons, and improve the foundation for studies of AOB circuit function.…”
Section: Implications Of Current Work For Models Of Aob Circuit Functionsupporting
confidence: 60%
“…2C, 3) may indicate an intermediate functional phenotype among IGCs. This hypothesis is partially supported by recent studies that showed IGC intrinsic physiology is altered over 2-8 hour time courses by recent chemosensory-driven activity (Cansler et al, 2017;Gao et al, 2017). It is an intriguing possibility that these other, more subtle, differences in IGC physiology may reflect their involvement in recent activation.…”
Section: Igc Physiological Diversity Suggests Multiple Functionally-dmentioning
confidence: 71%
See 2 more Smart Citations
“…It remains possible, however, that the intrinsic properties of participating neurons (passive membrane properties and composition of ion channels) also change during learning. Indeed, changes in ion channels have been observed in a variety of systems and there is a growing appreciation of the possibility of nonsynaptic forms of plasticity contributing to the learning process ( Debanne et al, 2003 ; Mozzachiodi and Byrne, 2010 ; Sehgal et al, 2013 ; Cansler et al, 2017 ). The present experiments explore changes in the intrinsic physiology of neurons in the zebra finch ( Taeniopygia guttata ) as juvenile birds progress through stages of vocal development.…”
Section: Introductionmentioning
confidence: 99%